Determinants of Accounting Students’ Career Choice in ERP: An Empirical Study - Isti Rahayu; Ambar Nurrina; Yestias Maharani (Mahesa Research Center, 2023)
One of the career paths possibly chosen by students in this digital era is the one in the area of information technology (IT), especially Enterprise Resource Planning (ERP). This research study aims to investigate the influence of financial rewards, job market considerations, work environment, professional training and professional recognition on career choice in the field of ERP-SAP. This research study makes use of primary data from the population of accounting students in the Special Region of Yogyakarta. From the population, a sample of 123 respondents is obtained by using convenience sampling. Based on the testing using PLS, the research findings reveal that the factors of financial rewards and job market considerations have a positive influence on career choice in the field of ERP. However, this research study cannot prove a positive influence of work environment, professional training, and professional recognition on career choice in the field of ERP-SAP. In the current technological era, Accounting Study Programs need to increase technological learning especially ERP, because it is considered by students as a career field that is still in high demand.